BETWEEN FORMULISM AND ENUMERATION: THE NOTIONS OF SPACE AND LIMIT IN MEDIEVAL CASTILIAN-LEONESE NOTARIES - Miceli, Paola (Revista de Historia Social y de las Mentalidades, 2016)
In recent years, scholars from various disciplines (history, geography, archaeology) have drawn attention to the gap between our conception of the space and that of the medieval men. Besides this, they have also pointed out the anachronism that involves studying the space in Middle Ages from our Cartesian points of view. In this context, we propose to analyze the lists and formulae appearing in notarial letters of donation and sale in Castile and Leon during the 12th and 13th centuries, to investigate their role and to establish the possible relationship between formulae and the ways in which medieval notaries demarcated the rights involved and conceived the space.